P-203 Orangeline: much more than expected. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Moss, Bridget; Scott, Jan; Freeman, Karen
Abstract : Background: OrangeLine, launched in April 2016, is a telephone helpline for local people seeking information, friendship and support. Callers do not have to be known to the hospice. OrangeLine addresses loneliness and isolation, and signposts to internal and external services. It was anticipated OrangeLine would run simply as a telephone helpline. Interventions are recorded and include all telephone and face to face contacts. In 2017 April recorded 122 interventions, and 186 in May. Aim: To gain feedback from service users after the first three months of the helpline, establish if OrangeLine is meeting their needs and make appropriate changes. To explore the impact of OrangeLine on service users. Method: Telephone user satisfaction surveys on the quality of the service, sought from each service user approximately two weeks after each call. Focus group participants, recruited from families who used family support services or OrangeLine. Thirty service users attended, diverse in age, gender and ethnicity, and feedback on quality of their experience was collected. Findings: Unanticipated needs were highlighted and included i)earlier and regular contact with OrangeLine, ii) immediate assistance with death certificate processes and iii) social contact with others in similar situations. Service design now includes a monthly social contact Friendly Faces group. Data from the satisfaction survey and the Friendly Faces group is analysed monthly and shows 92% feel less isolated and 83% feel their mood has improved. Condolence cards are sent out one week post bereavement to initiate earlier contact, followed by a welfare call one week later. Referrals from the inpatient unit are made immediately after death, to assist with death certificate administration. Conclusion: One year on, OrangeLine is much more than a telephone helpline. Service user feedback has directly impacted on redesign and delivery. The need for a formal service evaluation is being explored.